Evidence for On-Site Carboxylation in the Self-Assembly of 4,4′-Biphenyl Dicarboxylic Acid on Cu(111) - Schmitt, Tobias; Hammer, Lutz; Schneider, M. Alexander (Journal of Physical Chemistry C, 2016)
Molecular self-assembly at surfaces is controlled by a complex balance between molecule-substrate and intermolecular interactions. The occurrence of chemical reactions at the surface will alter the governing hierarchy of interaction energies substantially. An important aspect in this respect is whether the chemical reaction happens independently from the self-assembly process, such that reacted species form ordered structures, or whether the reaction is an integral part of the self-assembly process and is triggered during the formation of ordered structures. We report on a low-temperature scanning tunneling microscopy study of ordered phases of 4,4′-biphenyl dicarboxylic acid on Cu(111) at submonolayer coverage in ultrahigh vacuum. For this system the thermally activated carboxylation reaction influences the formation of molecular structures significantly. We find evidence that near room temperature the deprotonation of a molecule is triggered by the specific configuration of neighboring molecules allowing the formation of a complex, well-ordered structure combining intact and deprotonated molecules.
Created from Fastlane, Scopus look-up